2009
DOI: 10.1002/app.31004
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive removal of uranium from water by sulfonated phenol–formaldehyde resin

Abstract: Adsorption characteristics of a sulfonated phenol-formaldehyde resin (SPR) have been studied for U removal from aqueous solution by means of batch method. Adsorption experiments have been carried out as a function of contact time, solution/adsorbent ratio, particle size and pH. Adsorption isotherm has been evaluated by changing adsorbent dosage in the range of 0.04-80 g/L at an initial uranyl nitrate concentration of 0.05 mol/L. The enormous adsorption capacity of 0.29 mol/g estimated from the plateau region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…As one of the important actinide as a fuel in nuclear industry, the geochemical pathways of uranium is extremely important due to its long term toxic implications. Together with the other toxic metal ions such as Cu, Zn, Pb, Cd, and Hg, the removal of UO 2 2+ is extensively investigated [1][2][3][4][5][6][8][9][10]12,17,19,22]. Several techniques have been developed for determination uranium including spectrometry, neutron activation, spectrophotometer, molecular fluorescence spectrometry, gas chromatography, complex metric titration and voltammeter [22][23][24].…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the important actinide as a fuel in nuclear industry, the geochemical pathways of uranium is extremely important due to its long term toxic implications. Together with the other toxic metal ions such as Cu, Zn, Pb, Cd, and Hg, the removal of UO 2 2+ is extensively investigated [1][2][3][4][5][6][8][9][10]12,17,19,22]. Several techniques have been developed for determination uranium including spectrometry, neutron activation, spectrophotometer, molecular fluorescence spectrometry, gas chromatography, complex metric titration and voltammeter [22][23][24].…”
Section: +mentioning
confidence: 99%
“…The form of UO 2 2+ , UO 2 (OH) + , UO 2 (OH) 2 and UO 2 (OH) 3 from soil, rock, mines can exist and create environmental problems. The form of these metal ions is strongly depend on the pH of the medium and the presence of other ions [3,6,[8][9][10][11]. For the removal of UO 2 2+ from aqueous environments various materials such as clays, ion exchange resins, ashes, activated carbon and polymeric structures has been widely used [5,7,8,11].…”
Section: Introductionmentioning
confidence: 99%
“…The comparison obviously showed that these modified polymers synthesized in our laboratory should be considered amongst the favourite adsorbents. 13 Sulfonated phenol-formaldehyde 31 2-Acrylamido-2-methylpropane sulfonic acid 32 Amidoximated pine ibark 33 Poly(AAc/AAm)-cl-N,N-MBAAm 34 Chitosan/PVA hydrogel 35 Poly(acrylamidoxime-co-(1-(2-pirydylazo)-2naphtyl-2-methacrylate)-co-methacrylic acid) 36,37…”
Section: Reusability and Storage Abilitymentioning
confidence: 99%